Panama : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper provides background information to the IMF staff report for the 1996 Article IV Consultation discussions with Panama. It presents an overview of economic developments in Panama during 1995, focusing on areas of interest in Panama's medium-term economic strategy. It describes the changes in labor legislation aimed at increasing labor market flexibility. The paper summarizes developments in the tax system, focusing on the changes brought about by the Tax Incentives Harmonization Law of June 1995. The issues confronting the Panamanian social security system are also described.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet